Changes In Internal Organs Due to Exposure to Chronic Radiation Sickness (Eurasian Medical Research Periodical, 2024)
Chronic radiation sickness, resulting from prolonged exposure to ionizing radiation, poses significant health risks, including alterations in the structure and function of internal organs. This article examines the changes in internal organs associated with chronic radiation sickness, drawing upon insights from epidemiological studies, experimental research, and clinical observations. Through a comprehensive review of the literature, the article explores the pathophysiological mechanisms underlying radiationinduced organ damage, including cellular DNA damage, oxidative stress, inflammation, and tissue fibrosis. Specific organs affected by chronic radiation exposure, such as the hematopoietic system, gastrointestinal tract, cardiovascular system, and reproductive organs, are discussed in detail, highlighting the diverse manifestations of radiationinduced injuries and their clinical implications. Furthermore, the article addresses diagnostic modalities, therapeutic interventions, and preventive strategies for managing radiation-induced organ damage and mitigating long-term health consequences. By synthesizing current knowledge and research findings, this article provides valuable insights into the complex interplay between chronic radiation exposure and internal organ dysfunction, informing clinical practice, public health policy, and radiation safety guidelines.